A Study of the Quality of Work Life for the Staff of Greek Academic Libraries - Alvanoudi, Noula (Qualitative and Quantitative Methods in Libraries; Vol 9 No 3 (2020): September Issue 2020, 2020)
The present study focused on the quality of work life for Greek academic libraries staff. The role of factors related to the working time and the participants characteristics in levels of quality of work life were additionally studied. A sample of 144 employees of Greek academic libraries was tested with the Work – Related Quality of Life (WRQoL) Scale and with two questionnaires constructed for the study needs concerning their working time and individuals’ characteristics. According to the results, the WRQoL level was average for the participants. Although some differences were identified in the participants’ level of WRQoL with respect to the working time factors, these were not found to be statistically significant. In terms of individuals characteristics, it was found that the spouse/partner employment status, the library type, the job position and the department were significantly related to the quality of work life.